Plagiarism and Academic Dishonesty: Study of Users’ Perceptions in the University of Hyderabad - Suseela, V.J.; Uma, V. (Journal of Information and Knowledge, 2017)
Plagiarism is an ethical issue and has been universally disapproved, especially in the academic/ research/art and literary circles. The anti-plagiarism drive in the universities after the implementation of UGC regulations brought about changes in the academic community. This study examines users’ perceptions regarding plagiarism, plagiarism detection tools, similarity verification process and seeks to obtain their feedback on implementing the new practice in the University of Hyderabad and the role of the library in executing the program. This was done through an online questionnaire posted to all the students/research scholars who had got their work screened by the Library for plagiarism. The survey results indicate that around 80% of respondents were aware of the concept, functionality features of plagiarism detection tools, but mentioned their constraints in handling repeated terms, own publications etc. Further 80-90% agreed with implementing plagiarism detection process through tools and were satisfied with the information and screening services provided by the Library. Based on users expectations and results, it is suggested that institutions be proactive in promoting ethical values/ code among] students and in inculcating the best practices in writing.